PROSEDUR AUDIT UTANG USAHA PT.XYZ OLEH KANTOR AKUNTAN PUBLIK BHARATA, ARIFIN, MUMAJAD & SAYUTI - Julinia Rafadiah (2021)
Audit Procedures on Accounts Payable Accounts are a form of series in the audit process that cannot be eliminated. This procedure is carried out to ensure the correctness of the balance of accounts payable in the financial statements. Accounts Payable is an audit procedure activity carried out by KAP BAMS on PT. XYZ which is engaged in Construction and the procedure is carried out systematically in accordance with the standards issued by the Indonesian Accounting Association (IAI). In the process, KAP BAMS has complied with the applicable audit standards in Indonesia.